RANSOMWARE ATTACKS ON CRITICAL INFRASTRUCTURE: A STUDY OF THE COLONIAL PIPELINE INCIDENT - Srikanth Bellamkonda (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The Colonial Pipeline ransomware attack represented a watershed moment in critical infrastructure cybersecurity, exposing significant vulnerabilities in industrial control systems and their implications for national security. This comprehensive analysis examines the attack's progression, from initial compromise through recovery, highlighting its unprecedented impact on fuel distribution across the Eastern United States. The study investigates the technical, operational, and strategic lessons learned, emphasizing the importance of robust security controls, incident response procedures, and public-private sector collaboration. By analyzing the policy implications and subsequent regulatory changes, this research provides valuable insights into protecting critical infrastructure against evolving cyber threats while offering recommendations for enhancing organizational cybersecurity posture and resilience.